Study of Impact of Climate Change of Infectious Diseases: Assessing the Impact of Climate Change on Health Inequality in India (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The two-thirds of the Indian people are closely linked to livestock, fisheries and forests that are climate-sensitive. Extreme conditions, vector-borne pathogens and decreased crop yield are adversely affected. Indian climate change is vulnerable to a wide range of temperate areas, coastal megacities and 50 ° C deserts. The health effects of these weaknesses make uninhabited areas at risk of air contamination, infectious infections, malaria and cholera. The shortage of clean water combined with disease-carrying vectors exacerbates the health gaps and the risk of disease. As the second largest nation in the world with a shortage of adaptive ability and inadequate services and health facilities, 600 million people are at risk for infectious diseases and nutrition. India's limited allocation of climate financing to solve public health issues is unstable. The incorporation of social, socioeconomic and land-related data to define sustainable health options inside the health infrastructure and wide populations in India deserves an efficient climate change scenario framework. Climate consequences must be expected and successful strategies foreseen, which will undermine the right to health and raise health inequality in India.